2018
DOI: 10.1155/2018/5826174
|View full text |Cite
|
Sign up to set email alerts
|

The Dosimetric Impact of Shifts in Patient Positioning during Boron Neutron Capture Therapy for Brain Tumors

Abstract: Unlike conventional photon radiotherapy, sophisticated patient positioning tools are not available for boron neutron capture therapy (BNCT). Thus, BNCT remains vulnerable to setup errors and intra-fractional patient motion. The aim of this study was to estimate the impact of deviations in positioning on the dose administered by BNCT for brain tumors at the Tsing Hua open-pool reactor (THOR). For these studies, a simulated head model was generated based on computed tomography (CT) images of a patient with a bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…reduction due to SI or LR (lateral) shifts was significantly greater for smaller collimator sizes on both T 2.5 and T 6.5 and smaller CSD on T 2.5 , according to the Student's t-test. There were no significant differences in the DIs against both the AP shift and the lateral shift between the different T/B ratios and 10 B concentrations.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…reduction due to SI or LR (lateral) shifts was significantly greater for smaller collimator sizes on both T 2.5 and T 6.5 and smaller CSD on T 2.5 , according to the Student's t-test. There were no significant differences in the DIs against both the AP shift and the lateral shift between the different T/B ratios and 10 B concentrations.…”
mentioning
confidence: 76%
“…A cylindrical phantom (16 cm diameter × 20 cm height) similar to that used in the study of Lee et al 10 was modeled in the TPS.The phantom was made with homogeneous "Tissue soft" registered using RayStation. The mass density of the phantom was set to 1.000 g/cm 3 and was composed of hydrogen, carbon, nitrogen, and oxygen with elemental weights of 0.101, 0.111, 0.026, and 0.762, respectively.…”
Section: Phantom Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The need of a spatial realignment was highlighted by the non-negligible impact of patient positioning on the thermal/epithermal neutron flux estimation for dose planning. It was reported that a shift in patient positioning during treatment, but especially by set-up, has a relevant effect on dose estimation [ 14 ]. In fact, unlike conventional radiation therapies, sophisticated patient positioning tools are not available in BNCT.…”
Section: Multi-modal Imaging For Treatment Optimization and Response Evaluationmentioning
confidence: 99%
“…Furthermore, the positioning during imaging and during the treatment may be very different because the patient has to be brought directly to the rigid beam delivery system. It was found that a decrease in mean tumor dose results from high shift distances, and that dose distribution for brain tumors at greater depths would be more sensitive to patient motion [ 14 ].…”
Section: Multi-modal Imaging For Treatment Optimization and Response Evaluationmentioning
confidence: 99%